Endostatin Polymorphism 4349G/A(D104N) is not Associated with Aggressiveness of Disease in Postate Cancer. Issue 1 (9th June 2013) - Li, He Cheng; Cai, Qiu Yin; Shinohara, Eric T.; Cai, Hui; Cao, Carolyn; Fei Wang, Zuo; Teng, Ming; Zheng, Wei; Lu, Bo
Abstract : Endostatin is an important inhibitory molecule which mediates the sequential steps involved in angiogenesis. Lower level or impaired function of endostatin is associated with a higher risk of developing malignant solid tumors and with a worse prognosis of the disease. The endostatin N104 polymorphism might be associated with an impaired ability to inhibit angiogenesis. We analyzed the tissues from 98 Caucasian prostate cancer patients for the presence of D104N polymorphism. The frequencies of homozygous 4349G/G(104D/D), and heterozygous 4349G/A(104D/N) were 83.67%(82/98) and 16.33%(16/98), respectively; no individuals were homozygous 4349A/A(104N/N). With the Fisher's exact test we found the genotype of D104N was not significantly related to age, tumor grade, PSA and clinical stage ( P > 0.05). There was no difference in relapse free survival(RFS) or overall survival(OS) between patients with 104D/N and those with 104D/D ( P = 0.8283, 0.3713 respectively). We concluded that endostatin polymorphism was not associated with the aggressiveness of prostate cancer in Caucasian patients. Erratum of "Endostatin Polymorphism 4349G/A(D104N) Is Not Associated with Aggressiveness of Disease in Postate Cancer" dx.doi.org/10.1155/2005/318394